The adaptation to online learning during the COVID-19 crisis among students and instructors in College of Nursing, Christian University - Changmai, Sakul; Srisupornkornkul, Achara; Chonthong, Rattana (Thai Journal of Nursing, 2022)
This descriptive research aimed to study coping and adaptation to online learning during the COVID -19 crisis among students and instructors in College of Nursing, Christian University. A sample of hundred and ninety-one of students and instructors, were voluntarily selected. The research instruments included; 1) coping and adaptation questionnaires for students with the content validity index [CVI] of 0.87 and 0.83 and the Cronbach alpha coefficient of 0.78 and 0.95, respectively, and 2) coping and adaptation questionnaires for instructors with the CVI of 0.93 and 1.00, and the Cronbach alpha coefficient of 0.71 and 0.83. Data collection was done by using QR code and google form. Data were analyzed by descriptive statistics. The results showed that the coping with online learning of instructors was at the high level, while their adaptation was at the highest level. The coping with online learning and adaptation of students with Bachelor and diploma degree, were at the high level while those with Master’s degree, were at the highest level. The relationship between coping with online learning and adaptation in instructor group, was at the moderate level (r = 0.574) and in student group, it was at the high level (r = 0.660) at p < .01.